Quantifying the impact of fermented liquid bio formulations, biofertilizers and organic amendments on horticultural and soil nutrient traits of garden pea ( Pisum sativum L.) - Vandana Thakur; Praveen Sharma; Pradeep Kumar; Payal Sharma; Sartaj Ahmad Bhat; Sunny Sharma; Rehan Azmi; Shivender Thakur (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Modern agriculture heavily relies on the use of synthetic fertilisers, which are expensive and associated with significant environmental risks. Hence, it is necessary to focus on developing integrated farming practices that encompass cost-effective synthetic fertilisers. Method: The present experimentation was carried out to assess the effect of various treatments comprised of fermented liquid bio formulations, biofertilizers, & organic amendments on the horticultural, biochemical, & soil nutrient attributes of garden pea varieties. A Factorial Randomized Block Design was laid out for treatments in three replications. Results: The results of the investigation exhibited a significantly positive influence of the treatments and their interaction with pea varieties for most of the studied traits. Among varieties, treatments, and their interactions, variety GS-10 and PB-89 treatment modules, viz., Jeevmurta 20% + Phosphorus solubilizing bacteria 100% + Farmyard manure, and their interaction were found to be best for improving the various horticultural and soil traits i.e. shelling percentage, protein content, effective nodules per plant, available nitrogen and phosphorus content. However, the application of Jeevamurta 20 % + Rhizobium 100 % + Farm yard manure on pea variety GS-10, resulted a positive increment in yielding traits namely, plant height, number of pods per plant, single pod weight, total pod yield, pod yield per plant and pod yield per plot. Conclusion: The combination of variety “GS-10” with Jeevamurta 20%, Rhizobium 100%, and FYM, showed the positive increment in productivity of the garden pea, also found to be effective to control the incidence of rust and powdery mildew.